Making a Match : - Cook, Ann Jennalie (Princeton University Press, 2014)
Making a Match examines the various options posed at every stage of English wooing, together with the presentation of these protocols in the plays of Shakespeare. Across the canon, wooing may command either a casual reference or a central position in the action, but no play escapes a connection of some kind. Instead of taking a fixed position on an institution intended to stabilize the commonwealth, Shakespeare constantly shifts position, in a kaleidoscope of caricature, criticism, acceptance, subversion, or indifference. For general readers and specialists alike, this work supplies a rich understanding of the codes so familiar to the playwright and his audience–an understanding essential for an appreciation of the subtleties of his art. Delving into primary sources, social history, demography, and literary criticism, the author offers the widest possible range of both Renaissance and modern views on the most crucial experience of Elizabethan culture. Besides correcting or illuminating the interpretations of Shakespeareans, this book offers valuable material for any area of research on the English Renaissance that touches on courtship.Originally published in 1991.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
10.1515/9781400861750
Keywords: Courtship in literature.; Courtship; LITERARY CRITICISM / European / English; Irish; Scottish; Welsh.